Bioinspired Superhydrophobic Finishing of Cotton Fabric Using Carnauba Wax and Biosilica Nanoparticles with a Layer-by-layer Deposition Method - Mohamad Widodo; Rino Rakhmata Mukti; Sri Yuliani; Amalia Putri (Journal of Mathematical and Fundamental Sciences)
Hydrophobic surface modification has great potential for applications in everyday life, particularly in textiles such as sportswear, health, protection, and other non-clothing textiles. Improving water repellence and high-level hydrophobicity in textile materials has so far been difficult to achieve with chemicals other than PFAS (per- and polyfluoroalkyl substances) due to environmental and health concerns. In this research, biosilica nanoparticles from rice husk ash (RHA) and carnauba wax were deposited alternately using a layer-by-layer (LBL) method to create a surface with a combination of nanoscale roughness and hydrophobicity resembling the lotus effect. Chitosan was used to cationize the surface of cotton fibre and bridge the negatively charged nanobiosilica particles and carnauba wax. The hydrophobicity increased with the number of layers of nanosilica-chitosan-wax (SNP/CHI/SCW), reaching a contact angle of 140.2° (close to superhydrophobic) with three layers of SNP/CHI/SCW, followed by decreased air permeability from 19.4 cm3/cm2/s for untreated cotton to 13.3 cm3/cm2/s for treated cotton, with a total decrease of 31.44%. Cotton fabric was successfully modified from hydrophilic to superhydrophobic using an LBL coating of RHA silica nanoparticles and carnauba wax.